Exploration of the Influence of Ideological and Political Education on the Cultivation of Collaborative Spirit in Medical Teams - Huang, Xueying (Transactions on Social Science, Education and Humanities Research, 2024)
In the current medical field, teamwork has become a key factor in promoting the improvement of medical service quality and ensuring patient safety. However, team collaboration is not simply a collection, but requires shared goals, values, and deep trust and understanding among members. In this process, ideological and political education plays an irreplaceable role. This article aims to explore the impact of ideological and political education on the cultivation of cooperative spirit in medical teams. Through in-depth analysis of the ideological and political education issues in current medical team cooperation, corresponding solutions are proposed to improve the cohesion and collaboration efficiency of the medical team.